Influence of Temperature on Ultrasound Absorption and Structural Properties of Melts - S. Kazhikenova; G. Shaikhova; S. Shaltakov (Archives of Metallurgy and Materials)
Ultrasonic melt processing attracts considerable interest from both academic and industrial communities as a promising route improving melt quality. The significance of this problem is predetermined by the matter liquid state problem. In paper the ultrasound absorption and propagation speed vS temperature are measured using multiple groups of samples, each group heated to a different temperature. This paper summaries the results on the evaluation of ultrasound absorption and the propagation speed, for calculating the ultrasound propagation speed in solutions, studies of the nucleation, growth and fragmentation of particles in liquid melts. It has been proven that melts with semiconductor properties are micro-inhomogeneous due to the existence of clusters in their atomic matrix. These results provide valuable new insights and knowledge that are essential for upscaling ultrasonic melt processing to industrial level.